Emission lines from O IV as a plasma diagnostic - Dwivedi B.N.; Gupta A.K. (My University, 2025)
Using several density diagnostic O iv theoretical line ratios and corresponding observed values for the same source by Sandlin et al. (1984) and Sandlin, Brueckner, and Tousey (1977), we find that an emitting region has a multidensity structure. We discuss several other line ratios for density measurement in sunspots, active regions, and flares. © 1992 Kluwer Academic Publishers.